PENANGGULANGAN DELINQUENCY (KENAKALAN ANAK DAN REMAJA), DAMPAK DAN PENANGANANNYA - Winna A. Senandi; Tom A.S. Reumi (JURNAL PENGABDIAN PAPUA, 2018)
The titel of this research is Delinquency Prevention (Delinquency of Children And Youth), Impact And  Cured was held in SMK Negeri 7 and Muara Tami Junior High School Muara Tami District. The purposed of this research is to provide students with understanding of the forms of Delinquency, the factors causing Delinquency (Delinquency of children and teenagers) and how to handle it based on the laws and regulations in Indonesia. The method used is by counseling in the form of material exposure, discussion and question and answer. The result of this dedication is, the material given in the counseling about the Deliquency of Children is well received by the students and they are gives  good responses and responses  with various weighted questions asked during the counseling. Through this dedication is expected to be a preventive effort for the students  do not deeds belonging to Delinquency so as to prevent children or students from the legal problems that can arise from the delinquency of children and adolescents.Keywords: Countermeasures, Delinquency, Child, Adolescent, and Cured.